Family Livelihoods In Families Where The Husband Migrates For Work (An Empirical Study In Pematang Panjang Village, Lima Puluh Pesisir District, Batu Bara Regency) - Sukiati Sukiati; Sahmiar Pulungan; Tsaniyatul Akmal (Green Publisher Indonesia, 2024)
This study aims to explore the fulfillment of family livelihoods in families with migrating husbands in Pematang Panjang Village, Lima Puluh Pesisir District, Batu Bara Regency. This research used a qualitative approach with descriptive analysis method. The results showed that migrating husbands generally succeeded in fulfilling family maintenance responsibilities although there were variations in the fulfillment of certain types of maintenance, especially biological maintenance which was often hampered by distance. Fulfillment of household needs is mostly fulfilled, although there are variations depending on the needs of children's education and family financial management. The pattern of provision also varies, with the amount of maintenance received ranging from 1.5 million to 4.2 million per month. This study highlights the importance of communication and agreement between husband and wife in the management of maintenance, as well as the crucial role of the wife in educating the children while the husband migrates. The implementation of Islamic values and steadfastness in practicing worship become the main foundation in maintaining family harmony and stability despite the challenges of physical distance.